(untitled) (Nepalese Medical Journal, 2019)
Introduction: The burden of Overlap Syndrome (coexistence of sleep-related breathing disorders in patients with respiratory diseases) is high in developing countries, and such a phenomenon implies higher morbidity. The study was conducted to measure the prevalence of sleep-related breathing disorders in patients with Respiratory Symptom Complex and to identify factors associated with the severity of sleep-related breathing disorders. Materials and Methods: A hospital-based cross-sectional study of 50 patients with respiratory symptom complex was conducted at BP Koirala Institute of Health Sciences. Structured proforma and Polysomnography were used for analysis. Results: There were 24 patients (48%) with COPD, 18 (36%) with Bronchial Asthma. 6 patients (12%) with Bronchiectasis and 2 patients with Interstitial Lung Disease. 60% (n=30) patients had sleep-related breathing disorder or Overlap syndrome, 14 patients (46.67%) had mild sleep-related breathing disorder while 16 (53.33%) patients had moderate to severe type. 62.5% COPD patients, 55.55% Bronchial Asthma patients, 50% of patients with Interstitial Lung Disease and 50% Post-TB Bronchiectasis patients had a sleep-related breathing disorder. There was a significant positive correlation between the presence of sleep-related breathing disorder in patients with respiratory symptom complex and high neck circumference (0.499, p-value <0.001), waist circumference (0.293, p-value = 0.039) and hip circumference (0.371, p-value = 0.008). Conclusions: Overlap Disorders comprising sleep disorders in patients with chronic respiratory diseases are high in developing countries. Routine sleep history and polysomnography in all patients with Respiratory Symptom Complex can detect sleep-related breathing disorders.